Grade-Level Differences in Teacher Feedback and Students’ Self-Regulated Learning - Guo, Wenjuan (Frontiers in Psychology, 2020)
This study investigated grade level differences in teacher feedback, students’ self-regulated learning (SRL), and their relationship. Secondary students participated (N = 1,260; 430 tenth-, 460 eleventh-, and 370 twelfth-graders). Latent factor mean difference analyses suggested that teacher feedback and students’ SRL level varied across grades. Comparatively, tenth-grade teachers were perceived to provide verification feedback, scaffolding feedback, and praise most frequently; twelfth-grade teachers were perceived to provide directive feedback and criticism most frequently; and eleventh-grade teachers were perceived to provide all types of feedback least frequently. Students’ SRL generally declined as they aged. Results from three-group structural equation modelling indicated that praise generally had the strongest correlations with SRL regardless of grade level; directive feedback was negatively correlated with tenth-graders’ SRL but positively correlated with eleventh- and twelfth-graders’ SRL; scaffolding and verification feedback were positively correlated with eleventh-graders’ SRL; and criticism had small correlations with SRL, regardless of grade level.